Influence of elastic stresses and temperature on the dislocation unpinning from the stoppers in KCl crystals - Petchenko, G.A.; Petchenko, A.M. (Functional Materials, 2015)
Impulse echo-method was applied to investigate, in the temperature range from 300 to 430 K at 7.5 MGz frequency, the dislocation absorption αd(σ) in KCl crystals as a function of statistic loading in the quasi-elastic strain range. It has been found that the temperature increase at stresses σ < σt (σt is the yield strength of a crystal) leads to the intensive dislocation unpinning). Consequently, concentration of stoppers, controlling their motion, sharply decreases and the effective length of oscillating dislocation segments increases. As a result of the experimental data processing the energy of the impurity atom binding with dislocation U₀ and quantity L characterizing a mean size of the dislocation cell was calculated. The experimental results were discussed within the framework of known dislocation theories.